Crop Monitoring and Smart Farming Through Mobile App - M, Krishnamoorthy; K, Sakthisanjay; Nagajothi, P.; G, Sanjai (IRO Journal on Sustainable Wireless Systems, 2024)
This study presents the development and implementation of a mobile application aimed at revolutionizing crop monitoring and smart farming practices. The application integrates advanced technologies such as remote sensing and the Internet of Things (IoT) and provides real-time data analysis and decision-making support for farmers. By leveraging the ubiquity and accessibility of mobile devices, this solution enables farmers to remotely monitor crop health, soil conditions, and environmental parameters. Through intuitive interfaces and data visualization tools, the application empowers farmers to make informed decisions, optimize resource utilization, and enhance productivity in agricultural operations. This research highlights the potential of mobile technology to drive innovation and sustainability in modern farming practices.
Keywords: Real Time Monitoring; Mobile Application; Agricultural Innovation